Assessment of Large Animal Vascular Dimensions for Intra-Aortic Device Research and Development: A Systematic Review. Issue 2 (March 2023) - Georges, Gabriel; Couture, Thomas; Voisine, Pierre
Animal studies are often required to evaluate new cardiovascular medical devices before they reach the market. Moreover, first-generation novel devices including aortic endovascular prostheses and circulatory support devices are often larger than later iterations or tested in a limited range of sizes. One of the challenges in evaluating these devices is finding a model that is both accessible and anatomically similar to humans, as there is a paucity of data on vascular dimensions in large animals. We set out to complete a comprehensive review of available reports on vascular dimensions in swine, ovine, and bovine models, with a particular focus on the descending aorta and ilio-femoral arteries. We searched Embase and MEDLINE databases for reports of descending aorta and peripheral vascular dimension in large animal models. Data from swine, ovine, and bovine models were separated by weight into 3 categories: 40 to 60 kg, 61 to 80 kg, and >80 kg. We also incorporate our computed tomography angiography data from 4 large sheep and 9 calves into this review. Swine, sheep, and calf >80 kg may serve as the best models to maximize aortic diameter resemblance to humans. If device implantation can be achieved in aortas of smaller dimensions, care should be taken to ensure access site suitability such as the common femoral artery in these smaller animals. Visual abstract